2018
DOI: 10.1111/1745-9125.12198
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous effects of adolescent violent victimization on problematic outcomes in early adulthood*

Abstract: Violent victimization—particularly when it happens to young people—can inflict a wide array of negative consequences across the life course. Nevertheless, some victims are more likely to suffer these consequences than others, and we do not have a very good understanding of why that is. One promising avenue of research is to examine how individuals’ differential risks of being victimized affect the extent to which they experience negative outcomes. By using propensity score matching and data from the National L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
27
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 162 publications
7
27
1
2
Order By: Relevance
“…This finding does not fully align with previous cross‐sectional research, which highlighted greater psychological consequences of violence exposure for the most frequently victimised youth (Finkelhor et al, , ; Reid & Sullivan, ). However, our finding aligns with recent longitudinal research, which found significant heterogeneity in the impacts of victimisation (Turanovic, ). In this study, Turanovic () found “that the consequences of adolescent victimization in early adulthood are more pronounced for youth with the lowest risks of being victimized” (p. 1).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding does not fully align with previous cross‐sectional research, which highlighted greater psychological consequences of violence exposure for the most frequently victimised youth (Finkelhor et al, , ; Reid & Sullivan, ). However, our finding aligns with recent longitudinal research, which found significant heterogeneity in the impacts of victimisation (Turanovic, ). In this study, Turanovic () found “that the consequences of adolescent victimization in early adulthood are more pronounced for youth with the lowest risks of being victimized” (p. 1).…”
Section: Discussionsupporting
confidence: 92%
“…However, our finding aligns with recent longitudinal research, which found significant heterogeneity in the impacts of victimisation (Turanovic, ). In this study, Turanovic () found “that the consequences of adolescent victimization in early adulthood are more pronounced for youth with the lowest risks of being victimized” (p. 1). Similar to these findings, this study provides support for the “disadvantage saturation” hypothesis (Hannon, ; Turanovic, ), which proposes that the harmful effects of any singular stress or adversity are attenuated for those who are exposed to multiple adversities or for the “stress inoculation” explanation (Lyons, Parker, Katz, & Schatzberg, ), which suggests that the process of coping with stress builds resilience.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Recent research has developed approaches to model "treatment-effect heterogeneity" using propensity scores, based on the idea that those factors which were influential for the selection of individuals into treatment (in this case, victimization) may also moderate the treatment effects (Brand and Thomas 2013;Xie et al 2012). Applying this approach to Add Health data, Turanovic (2019) found that victimization effects were strongest for those with the lowest propensity to be victimized, and reversely, weakest for those with the highest propensity, which she interpreted as a "disadvantage saturation" effect. In contrast, Mahuteau and Zhu (2016) reported stronger detrimental effects of victimization on wellbeing for those individuals who were in the lowest decile of the well-being distribution, and no significant effects for those at high levels of well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Among delinquent adolescents and particularly in neighborhood contexts of concentrated disadvantage and possibly subcultural norms, victimization has been found to actually increase risky lifestyle activities (Turanovic et al 2018). Thus, behavioral reactions to victimization could depend on individual and contextual differences which in themselves seem relevant for the likelihood of victimization, a phenomenon which is discussed as treatment-effect heterogeneity (Brand and Thomas 2013;Turanovic 2019).…”
Section: Negative Consequences Of Victimization and Other Life Eventsmentioning
confidence: 99%